Toward Quality Online Physical Education: Research Questions and Future Directions. (2nd October 2022) - Daum, David N.; Goad, Tyler; Mosier, Brian; Killian, Chad M.
ABSTRACT: Before the COVID-19 pandemic, online education had grown steadily over the past decade as more K-12 schools and districts expanded their educational options. This included the use of virtual school days, hybrid learning, and fully online courses. Enrollments in K-12 Online Physical Education (OLPE) had also increased steadily over the past decade, representing almost ten percent of total online course completions (Distance Learning Collaborative (DLC), (2019 ). The purpose of this article is to present a coherent agenda for future research related to K-12 OLPE using current research as a foundation. The Society of Health and Physical Education (SHAPE) America's Essential Components of Physical Education served as the framework for this article. Overall, limited research has been conducted regarding the policies and decisions that drive the development and implementation of OLPE. Current research does, however, provide some clarity related to OLPE curriculum, instructional practices, and student assessment. K-12 OLPE is not an abstract idea that might come about in the future. It is part of the here and now, especially considering the shift toward distance learning due to the COVID-19 pandemic. Scholars must cultivate a coherent research agenda and move beyond the current exploratory studies to answer some of the most poignant questions surrounding OLPE.